Revisiting the time-varying credit rating policy: a new test of procyclicality. Issue 10 (6th June 2020) - Hwang, Daniel; Kim, Yongjun
ABSTRACT: This article investigates whether agencies' rating policy varies over macroeconomic cycle. We develop a novel two-stage estimation procedure to find that the rating policy becomes more strict after economic downturn than expansion, consistent with theoretical predictions. Moreover, from the horse race between various macroeconomic indicators, we find that the default spread serves as the strongest indicator for the time variation of rating standard.